A Fourier-Transform Infrared Spectroscopy-Based Simple, Rapid, and Direct Quantification Assay for Moxifloxacin - Muhammad Umair Kamal; Sumia Akram; Muhammad Ahmad Khan; Atique Ur Rehman; Muhammad Ehsan Ameer; Raja Adil Sarfraz; Asif Iqbal; Rizwan Ashraf; Muhammad Mushtaq (Journal of Spectroscopy)
In the present study, a partial least square regression (PLSR) was applied to Fourier-transform infrared (FTIR) data for rapid and direct quantification of a quinolone family antibiotic moxifloxacin and the proposed method was counter validated by reverse-phase high-performance liquid chromatography under diode array detection (RP-HPLC-DAD). The PLSR-based processing of FTIR spectra of moxifloxacin standards and formulations disclosed a concentration-dependent mid-IR region at 1456 cm−1. The FTIR-based assay method was validated in accordance with the International Conference on Harmonization (ICH) guidelines and was found to be linear over the concentration range of 0.1 mg/mg–1.0 mg/mg (w/w) of solid mixtures with a coefficient of determination (R2) of 0.9951. Moreover, the results when counter validated by RP-HPLC-DAD were found to be concordant (RSD ≤ 2%). The analysis of moxifloxacin quality control samples through the developed FTIR assay offered overall recovery rates equals to 97.61%–103.74%. The real-time analysis of moxifloxacin formulations marketed in Pakistan authenticated the presence of active pharmaceutical ingredients (APIs) within the claimed ranges. We can eventually conclude that FTIR spectroscopy if coupled with a suitable data-processing scheme can provide more expedient, rapid, and economical choice for the direct quantification of moxifloxacin API and its formulations.